A Study on physical separation processes for recovery metals from Waste Printed Circuit Boards (PCBs) - Aimi Noorliyana Hashim (School of Materials Engineering, University Malaysia Perlis, 2011)
This research is aimed to implement an effective and environmental friendly recovery particularly cooper (Cu) of waste PCBs.